Manejo contable de los pasivos de la farmacia su receta, de la ciudad de Babahoyo, periodo 2022 - Rivera Quinto, Shirley Xiomara (2023)
Within a company it is essential that accounting processes are carried out; for its proper financial development. Therefore, in the following case study, the objective was to determine the accounting management of the liabilities of Su Receta pharmacy, in the city of Babahoyo, period 2022, through the review of accounting information. The methodology for the study is qualitative, descriptive, bibliographic, its technique was given by the application of the interview and the documentary review of the financial statements of the company. The results showed that the pharmacy has problems in the accounting management of liabilities, since it does not have a defined accounting system, nor does it have a support system for the accounts, to this is added that the liabilities in the period 2022, exceeded the assets, which means that covering debts became difficult. In conclusion, it was evidenced that in Su Receta pharmacy, there is a considerably high degree of indebtedness, this was obtained through the application of the indebtedness index ratio.